IMPROVING THE ANALYSIS OF FINANCIAL STATEMENTS IN COMMERCIAL BANKS (World Economics and Finance Bulletin, 2023)
This article explores strategies for improving the analysis of financial statements in commercial banks. It employs a multi-faceted approach, encompassing key financial ratios, trend analysis, and advanced data analytics techniques.
Keywords: Financial statement analysis; commercial banks; key financial ratios